Advanced Ceramic Processing - Mohamed, Adel (IntechOpen, 2015)
Ceramic oxides typically have a combination of properties that make them attractive for many applications compared with other materials. This book attempts to compile, unify, and present a recent development for the production techniques, such as electrochemical, foaming, and microwave sintering, of rare earth ceramic oxide materials. This book presents leading-edge research in this field from around the world. Although there is no formal partition of the book, the chapters cover several preparation methods for ceramic oxides, especially for coating and electrical applications. In addition, a fabrication foaming technique for porous ceramics with tailored microstructure along with distinctive properties is provided. The information provided in this book is very useful for a board of scientists and engineers from both academia and industry.